2004
DOI: 10.1103/physrevd.69.054027
|View full text |Cite
|
Sign up to set email alerts
|

Unphysical operators in partially quenched QCD

Abstract: We point out that the chiral Lagrangian describing pseudo-Goldstone bosons in partially quenched QCD has one more four-derivative operator than that for unquenched QCD with three flavors. The new operator can be chosen to vanish in the unquenched sector of the partially quenched theory. Its contributions begin at next-to-leading order in the chiral expansion. At this order it contributes only to unphysical scattering processes, and we work out some examples. Its contributions to pseudo-Goldstone properties beg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…18 17 We note that the vector hairpin is poorly determined from the MILC data, and that effects of the vector and axial vector hairpins are, in practice, difficult to disentangle in SχPT fits. 18 The explicit expression for B K in terms of B K is given in Eq.…”
Section: Guide For Lattice Determination Of B Kmentioning
confidence: 99%
See 1 more Smart Citation
“…18 17 We note that the vector hairpin is poorly determined from the MILC data, and that effects of the vector and axial vector hairpins are, in practice, difficult to disentangle in SχPT fits. 18 The explicit expression for B K in terms of B K is given in Eq.…”
Section: Guide For Lattice Determination Of B Kmentioning
confidence: 99%
“…This is relatively straightforward; we follow the graded group-theory method of Refs. [10,17] to insure that we include all possible linearly-independent operators. This results in two operators, Eqs.…”
mentioning
confidence: 99%
“…Second, some of the mesons have more complicated propagators due to hairpin diagrams at the quark level [51,55]. Third, there are additional terms in the NLO Lagrangian which arise from partial quenching [52], and lattice spacing effects [10,38].…”
Section: B Mixed Gw-staggered Theory With Two Sea Quarksmentioning
confidence: 99%
“…[41,42] to MAPT. A mixed action simulation necessarily involves partially quenched QCD (PQQCD) [47][48][49][50][51][52], in which the valence and sea quarks are treated differently. Consequently, we provide the PQPT scattering amplitude by taking an appropriate limit of our MAPT expressions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the O p 4 Lagrangian has one additional operator as compared to the Gasser-Leutwyler Lagrangian. However, we do not need to consider the effects of this operator in our analysis as it has been shown that it can be constructed such that it does not contribute to valence quantities until O p 6 [60]. This is not generally the case, as is demonstrated by various examples in the baryon sector [61][62][63][64][65][66][67][68][69][70].…”
mentioning
confidence: 99%